Multicolor Emission of Hybrid Block Copolymer–Quantum Dot Microspheres by Controlled Spatial Isolation of Quantum Dots. Issue 16 (7th February 2013) - Ku, Kang Hee; Kim, Minsoo P.; Paek, Kwanyeol; Shin, Jae Man; Chung, Sunhaeng; Jang, Se Gyu; Chae, Weon‐Sik; Yi, Gi‐Ra; Kim, Bumjoon J.
<x xml:space="preserve">Abstract</x> Multicolor emitting microspheres with three dimensionally controlled nanostructures are produced via a simple and efficient method. Location control and separation of the quantum dots (QDs) within the microspheres are achieved by a supramolecular assembly of block copolymer micelles to control the Förster resonance energy transfer efficiency between the different‐colored QDs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>